2001
DOI: 10.1021/jp001254+
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Reactivity of Gaseous Nitric Acid on Al2O3, CaCO3, and Atmospheric Dust Samples:  A Knudsen Cell Study

Abstract: The heterogeneous reaction between HNO 3 and various authentic and synthetic mineral dust/mineral oxide surfaces has been investigated using a low-pressure Knudsen reactor operating at 298 K. The surfaces used were Saharan dust from Cape Verde, Arizona dust, CaCO 3 , and Al 2 O 3 . In all cases, a large irreversible uptake was observed. An uptake coefficient of γ ) (11 ( 3) × 10 -2 was determined for Saharan dust, and γ ) (6 ( 1.5) × 10 -2 was obtained for Arizona dust. The uptake coefficients for HNO 3 on hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 40 publications
13
113
6
Order By: Relevance
“…Prospero et al, 1981) and confirmed by laboratory measurements (e.g. Hanisch and Crowley, 2001). The remaining part of the NO − 3 is found on particles between 0.8 and 1.7 µm, which are probably the smallest sea-salt particles.…”
Section: Aerosol Compositionsupporting
confidence: 53%
“…Prospero et al, 1981) and confirmed by laboratory measurements (e.g. Hanisch and Crowley, 2001). The remaining part of the NO − 3 is found on particles between 0.8 and 1.7 µm, which are probably the smallest sea-salt particles.…”
Section: Aerosol Compositionsupporting
confidence: 53%
“…HNO 3 in the atmosphere is taken up by mineral dust particles as nitrates, reducing photochemically active NO x (Hanisch and Crowley, 2001;Underwood et al, 2001;Liao et al, 2003;Gibson et al, 2006b). As a result, mineral dust particles in northern China can affect photochemical oxidation in the regional atmosphere.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Laboratory studies suggest increased uptake coefficients of HNO 3 , NO 2 , and SO 2 gases on mineral dust under higher relative humidity (which determines the amount of water associated with the particles) [Dlugi et al, 1981;Goodman et al, 2000;Hanisch and Crowley, 2001;Underwood et al, 2001;Usher et al, 2002]. Thus, to accumulate the comparable cases under various atmospheric conditions, observations should preferably be made in more stationary air with a constant supply of dust and pollution, such as in the urban boundary layer.…”
Section: Introductionmentioning
confidence: 99%